Effectiveness of Group Guidance Services with Rational Emotive Imagery (REI) Techniques to Reduce the Identity Crisis of Students at MTS Islamiyah Londut - Mawaddah, Firda Aulia; Syarqawi, Ahmad (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study aims to reduce the identity crisis experienced by students at MTs Islamiyah Londut. Using a quantitative research method, where in this study used a sample of class VII with a population of 30 people, this study involved two groups, namely the Experimental group totaling 15 people and the control group totaling 15 people. The Experimental group was given treatment guidance, group guidance, with (REI). This is evident from the results of the initial pretest of the experimental group which showed a score of 62 and increased to 67.3 after participating in group guidance using the Rational Emotive Imagery (REI) technique. Because most of the instruments used in the survey were negative, which means a higher score means a reduced identity crisis. It can be concluded that group guidance services using the Rational Emotive Imagery (REI) technique at MTs Islamiyah Londut can reduce student identity crises.